A proposed customer-based brand equity model for the halal food industry - Ahamat, Amiruddin; Md Saad, Nurul Huda; Robani, Anidah (Inderscience Publishers, 2024)
Muslim consumers are working harder to make sure that the brand they purchase is tracked throughout the supply chain. Food businesses must uphold Shariah-compliant practises in harmony with their brand. The purpose of this study is to present a conceptual model of halal food brand equity as a trusted value for customers. The research focuses on how to build a halal food brand using established brand equity components: halal brand awareness, halal perceived quality, halal brand association, and halal brand loyalty, as well as how to mediate the halal food supply chain's integrity image architecture. According to research of Muslim consumers in the halal food industry, the positive impact of the integrity of the halal food supply chain on choosing halal food brands is a critical factor in ensuring that food is produced ethically. Suggestions have been made for studies on a halal food consumer-based brand equity approach, which is unique to the halal food industry.